Search for 1-10 Hz Modulations in Coronal Emission with SECIS during the August 11, 1999 Eclipse - GALLAGHER, PETER THOMAS (EDP Sciences, 2004)
Results of the search of the periodic changes of the 530.3 nm line intensity emitted by selected structures of the solar corona in the frequency range 1-10 Hz are presented. A set of 12 728 images of the section of the solar corona extending from near the north pole to the south-west were taken simultaneously in the 530.3 nm ("green") line and white-light with the Solar Eclipse Coronal Imaging System (SECIS) during the 143-seconds-long totality of the 1999 August 11 solar eclipse observed in Shabla, Bulgaria. The time resolution of the collected data is better than 0.05 s and the pixel size is approximately 4 arcsec. Using classical Fourier spectral analysis tools, we investigated temporal changes of the local 530.3 nm coronal line brightness in the frequency range 1-10 Hz of thousands of points within the field of view. The various photometric and instrumental effects have been extensively considered. We did not find any indisputable, statistically significant evidence of periodicities in any of the investigated points (at significance level $\alpha=0.05$).
PUBLISHED
Keywords: Astrophysics